Comparison of the structural and functional properties of starches in rice from main and ratoon crops. (May 2021) - Zhang, Wei; Luo, Xianli; Zhan, Zhan; Shu, Zaixi; Wang, Pingping; Ding, Wenping; Zeng, Xuefeng; Shi, Yong-Cheng
Abstract: Ratooning has become a practical approach to produce additional rice grain. The objectives of this study were to investigate and compare the structure, pasting properties and digestibility of the starches from main and ratoon rice. The starches in the two ratoon crops had a higher amylose content (14.87% and 16.40%) than that in the main crops (8.40% and 9.90%). Ratoon crop starch also contained a higher proportion of short chains (degree of polymerization, DP 6–24) and a lower proportion of long chains (DP ≥ 25) in its amylopectin, and exhibited a lower short-range order. Both main and ratoon crop starches had an A-type crystalline structure, but the latter showed reduced relative crystallinity. Compared with main crop starch, starch in the ratoon crop had decreased lamellar peak intensity in the small angle X-ray scattering pattern, a lower volume-average diameter, a lower pasting temperature and decreased peak and breakdown viscosities but increased setback viscosity. Cooked ratoon crop starches had a lower resistant starch content despite their higher amylose content. These results are helpful in understanding the differences in quality between main crop and ratoon crop rice and can provide basis for promoting the ratooning cultivation mode of rice. Graphical abstract: Image 1 Highlights: Structures and properties of starches from main and ratoon crop rice were compared. Ratoon crop starch had a higher amylose content than main crop starch. As Indica rice, main crop starches had unusually low amylose contents (8–10%). Ratoon crop starch had a lower relative crystallinity than main crop starch. Cooked ratoon crop starches contained a lower resistant starch content.